Advanced Adsorbent Materials: Electrospun PS/fGO/PPy Membranes for Efficient Dye Removal from Aqueous Media - Lúcio F. M. Cavalcanti; Winnie Q. Brandão; Andressa N. R. Leal; Maurício F. de Aguiar; Etelino F. de Melo; Celso P. de Melo; Joanna. E. K. Barros; Lucas R. de Oliveira; Bráulio S. Barros; Kleber G. B. Alves (Materials Research)
We synthesized and characterized electrospun polystyrene (PS) membranes functionalized with graphene oxide (fGO) and polypyrrole (PPy) for the removal of Eriochrome Black T (EBT) dye from aqueous media. The membranes were prepared via electrospinning, followed by air plasma treatment to improve hydrophilicity, enabling uniform coating with fGO and in situ polymerized PPy. Characterization using SEM, XRD, FTIR, and UV-Vis spectroscopy confirmed the successful incorporation of fGO and PPy. Adsorption experiments evaluated the effects of pH, interaction time, dye concentration, temperature, and ionic strength. The highest adsorption capacity (qe) of 110 mg g−1 was achieved at pH 2 and room temperature, with equilibrium in 150 minutes. Kinetic and isotherm modeling indicated that adsorption follows the pseudo-second-order and Langmuir models, suggesting monolayer adsorption. The thermodynamic analysis confirmed an endothermic and spontaneous process, with a maximum qe of 473.3 mg g−1 at 333 K. The membrane remained effective for at least six adsorption/desorption cycles, and adsorption efficiency increased in saline solutions, demonstrating its potential for real wastewater treatment.